Sustainable Development of Employees as the Foundation of the Company’s Progress - Žnidaršič, Jasmina; Bernik, Mojca (Management skozi prizmo digitalnega in zelenega prehoda v družbo 5.0, 2025)
Sustainable employee development is key to creating an environment that promotes long-term employee satisfaction and performance and contributes to the sustainable development of society. The development of employee competencies also contributes to organizational goals in the context of sustainable development. The paper presents in more detail the case of preparation of a competence model, which would serve in the future for the purposes of evaluation and reward, thereby improving the motivation and productivity of employees. The individual steps of building a competency model are shown, including a set of general and work-specific competencies, as well as the final description of competencies. With the help of a competency model, organizations can better understand the needs of their employees, identify key competencies for success in specific roles, and plan and implement effective development programs.